Early Marriage Among Teenagers in Peniti Dalam II Village, Segedong Subdistrict, Mempawah Regency - Desita Sari; Endang Indri Listiani; Syarifah Ema Rahmaniah; Mukhlis, Mukhlis; Syarmiati, Syarmiati (International Journal of Education, Vocational and Social Science, 2024)
Early marriage in the Peniti Dalam II Village Community is quite common. The causes of early marriage in Peniti Dalam II Village are promiscuity, avoiding adultery, pregnancy outside of marriage, self-will, culture, invitations have been spread, broken home children, and because they have been dating for a long time. The puspose of this research is to explain the causes of early marriage and the impact of early marriage in the Peniti Dalam II Village, Segedong District, Mempawah Regency. The method used in this research is descriptive qualitative reseacrh method with observation, interview, and dokumentation techniques. The results of this study indicate that the negative impact is more dominant in early marriages conductred by teenagers in Peniti Dalam II Village.